PENGARUH ARUS KAS OPERASI, TINGKAT UTANG, DAN AKRUAL TERHADAP PERSISTENSI LABA DENGAN BOOK TAX DIFFERENCES SEBAGAI VARIABEL MODERATING (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - ,Nanda Fito Mela, Yulia Elfitasari ,Nasrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to examine and analyze the effect of operating cash flow, leverage and accruals on earnings persistence and to test and analyze the effect of operating cash flows, leverage and accruals on earnings persistence moderated by book tax differences. The period in this study is 4 years from 2018-2021, this study uses secondary data in the form of financial reports and annual reports. The technique used in this research is purposive sampling, this study uses multiple analysis. From the results of the tests that have been carried out, it shows that operating cash flow has an effect on earnings persistence while leverage and accruals have no effect on earnings persistence, for variables moderated by book tax differences, it shows operating cash flow and leverage have an effect while accruals have no effect. Keywords: operating cash flow, leverage, accruals, earnings persistence, book tax differences.